A metal organic foam-derived multi-layered and porous copper sulfide scaffold as sulfur host with multiple shields for preventing shuttle effect in lithium-sulfur batteries. (1st October 2020) - Long, Jiawei; Zhang, Haikuo; Ren, Jiahao; Li, Jinjin; Zhu, Mengfei; Han, Tianli; Sun, Bai; Zhu, Shuguang; Zhang, Huigang; Liu, Jinyun
Abstract: Huge volume-change of sulfur and the shuttle effect of polysulfides during charge-discharge severely restrict the electrochemical performance of lithium-sulfur (Li-S) batteries. Herein, we present a novel three-dimensional (3D) multi-layered and porous CuS scaffold derived from metal organic foams (MOFs) as high-performance sulfur host for Li-S batteries. The CuS/S composites enable an optimal environment for accommodating the volume-change of sulfur, and the multiple CuS layers form several shields to prevent the loss of sulfur and polysulfides, efficiently suppressing the shuttle effect. The batteries based on the CuS/S composites exhibit a stable capacity of 750 mAh g −1 after 200 cycles at 0.1 C, and a well-recoverable rate-performance after being tested for three rounds repeatedly. Furthermore, density functional theory (DFT) calculations confirm the novel sulfur host exhibits a strong adsorption ability to polysulfides with large adsorption energies and charge transfers towards Li2 S4, Li2 S6, and Li2 S8 . Graphic abstract: Image, graphical abstract